2008
DOI: 10.1002/jemt.20658
|View full text |Cite
|
Sign up to set email alerts
|

Research on precision‐calibration techniques for selected area electron diffraction patterns of pyrocarbon

Abstract: The key techniques for determining orientation angle (OA) and interlayer space (d002) of pyrocarbon were investigated by analyzing selected area electron diffraction (SAED) patterns. A series of algorithms, which mainly include the five-point center-determined technique, the integral factor for the ellipse detection, the background subtraction operation and the Gaussian multipeak fitting algorithm, were designed for intensity sampling, data correction, and data fitting. The contribution ratio of the reflection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…TEM images clearly showed that the surface of the C f was covered with a thin and uniform interfacial layer with a thickness of about ∼150 nm (Figure 4(a)). From the SAED pattern and based on the procedures preparation by our research group [24], orientation angle (OA) value of 88° could be obtained, which demonstrated that PyC in our samples would be considered low texture [25].
Figure 4 (a) TEM image of the fibres coated with PyC, (b) the corresponding SAED diffraction pattern, and (c) OA value.
…”
Section: Resultsmentioning
confidence: 91%
“…TEM images clearly showed that the surface of the C f was covered with a thin and uniform interfacial layer with a thickness of about ∼150 nm (Figure 4(a)). From the SAED pattern and based on the procedures preparation by our research group [24], orientation angle (OA) value of 88° could be obtained, which demonstrated that PyC in our samples would be considered low texture [25].
Figure 4 (a) TEM image of the fibres coated with PyC, (b) the corresponding SAED diffraction pattern, and (c) OA value.
…”
Section: Resultsmentioning
confidence: 91%